Flexural and Bond Behavior of Concrete Beams Strengthened with Fiber-Reinforced Polymer Sheets - Muhammad, Hussein; Mohd Isa, Haziq Najmi; Abdul Kudus, Sakhiah; Mohammed, S. Haji Sheik; V. Roopa (International Journal of Integrated Engineering, 2024)
Concerns have been expressed regarding the issue of using conventional steel rebar in civil engineering structures. One contributing factor is the corrosion that occurred on the steel rebar. The corrosion process was not promptly detected due to the gradual reaction time exhibited by the steel, concrete, and environmental conditions. Corrosion problems often manifest when corrosion has progressed to a critical point and damaged the concrete structure. Consequently, to address this issue, this research proposed the application of carbon-fiber reinforced polymer sheet (CFRP). The aim is to measure the flexural load of conventional and FRP-reinforced concrete beams, to test the effects of cracking and deflection on concrete beams strengthened with FRP sheet, and to determine the degree to which these loads damaged these beams. A repair method was implemented by applying two distinct diameters of CFRP: 50 mm × 100 mm and 100 mm × 200 mm. The finding shows that the concrete beam’s significantly higher flexural strength resistance was observed for CFRP of greater dimensions. This is mostly because the CFRP can disperse the applied stress more effectively. Alternative applications of fibre-reinforced polymer should be explored for further research to facilitate the development of substitutes for CFRP.